2006
DOI: 10.4102/sajhrm.v4i1.78
|View full text |Cite
|
Sign up to set email alerts
|

A Model Of The Underlying Philosophy And Criteria For Effective Implementation Of Performance Management

Abstract: The objective of this study was to develop a model that assists organisations in implementing performance management effectively. A model describing the philosophical paradigm underpinning best practice in performance management and the criteria for effective implementation of performance management was developed. The sample used in this study was a convenience sample of 615 employees. Exploratory factor analysis revealed three reliable philosophical dimensions. Moderate correlations were found between the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Despite their importance and prevalent use, the implementation of performance appraisals is frequently defective in a number of ways. These limitations include erroneous judgements about performance, unproductive feedback, invalid performance criteria and a lack of transparency about the purpose of the system (Maley & Kramar, 2007;Whitford & Coetsee, 2006). At the same time, a performance appraisal cannot be an exclusive process, and the consequences of the appraisal may infl uence a number of human resource management areas (Rousseau, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite their importance and prevalent use, the implementation of performance appraisals is frequently defective in a number of ways. These limitations include erroneous judgements about performance, unproductive feedback, invalid performance criteria and a lack of transparency about the purpose of the system (Maley & Kramar, 2007;Whitford & Coetsee, 2006). At the same time, a performance appraisal cannot be an exclusive process, and the consequences of the appraisal may infl uence a number of human resource management areas (Rousseau, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…At the Australian national level, the criteria for performance appraisal have received a great deal of attention from researchers and have been broadly divided into results and behaviours. Results are easily defined and can lead to superior productivity and business goals (Whitford & Coetsee, 2006). However, this approach has a number of shortcomings (McGovern, 1999;Muchinsky, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Milliman et al (2002) argue that the purpose of appraisal has fallen short not only in the USA but in ten other countries they sampled. Whitford and Coetsee (2006) examined appraisal in a large life insurance firm in South Africa and they also found that the appraisal purpose was frequently unclear to employees. They recommended that MNCs need to devote more time and effort to managing the purpose of appraisals.…”
Section: Performance Appraisalmentioning
confidence: 99%